Study the effect of fish in alternating electrical properties of copper oxide membranes CuO - Baghdad Science Journal (مجلة بغداد للعلوم, 2006)
In this research study the effect of fish in alternating electrical properties at room temperature copper oxide membranes and fish prepared in a manner different thermal spraying chemical on a thin glass bases and heated